Suppression of Botrytis cinerea by antagonists in living, moribund and dead grapevine tissue - Volkmann, Anette (Anette Sigrid) (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScAgric)--University of Stellenbosch, 2001.